Spatial distribution and long-term trend of wind energy in the Northwest Pacific Ocean - Kaishan Wang; Di Wu; Tao Zhang; Lei Yin; Kai Wu; Chongwei Zheng (Water-Energy Nexus)
Abstract: Given the threat of fossil fuel depletion, it is essential to proactively strive for carbon neutrality and promote clean, low-carbon and efficient energy use. This study used ERA5 reanalysis data to assess wind energy resources in the Pacific Northwest region. By analyzing key indicators such as wind power density, effective wind speed occurrence, and energy level occurrence, climate statistics and empirical orthogonal function analysis (EOF) were used to examine the spatial distribution and long-term trend of offshore wind energy resources in the Northwest Pacific. The results suggest that there are abundant wind energy resources in this region, which are beneficial for the development of offshore wind energy. The rich areas are the East China Sea, Taiwan islands and reefs in the South China Sea and the eastern shore of Japan, with prevailing wind power density (500 ∼ 2500 W/m2) and effective wind speed occurrence (80–90%) and energy level occurrence (60% ∼ 90%). Offshore wind energy resources in the Pacific Northwest are more abundant in fall and winter than in summer. The time coefficient of the first mode shows that the offshore wind energy in the Northwest Pacific has no obvious change trend, and the wind energy resources are relatively stable.